2019
DOI: 10.1007/s00702-019-02019-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric aspects of Parkinson’s disease

Abstract: Throughout the natural history of Parkinson's Disease (PD), from the pre-diagnostic phase to end stage disease, neuropsychiatric manifestations represent a core feature of the disease. This review summarises current knowledge on the features of depression, anxiety, apathy, fatigue, impulse control disorders (ICDs) and psychosis in PD. These co-morbidities are common and still frequently under-recognised. Their impact on quality of life is considerable, with depression having been shown to be the main determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 99 publications
2
20
0
Order By: Relevance
“…Focusing on the S‐depression subtype, we found widespread disrupted functional connectivity both within the motor‐ and depression‐related connectivity patterns as well as outside of these two patterns, covering the frontal‐temporal and parietal‐occipital regions. Several studies demonstrated that the neural bases of depression in PD patients was likely to be diffuse, and has been referred to as disrupted structure or function in frontal, temporal and occipital regions (Feldmann et al, 2008; Gou et al, 2018; Mayberg et al, 1990; Nagy & Schrag, 2019), which corresponded with our findings and indicated serious brain damage in the S‐depression subtype. Additionally, enhanced functional connectivity in the cerebellum and thalamus was also observed in the S‐depression subtype.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Focusing on the S‐depression subtype, we found widespread disrupted functional connectivity both within the motor‐ and depression‐related connectivity patterns as well as outside of these two patterns, covering the frontal‐temporal and parietal‐occipital regions. Several studies demonstrated that the neural bases of depression in PD patients was likely to be diffuse, and has been referred to as disrupted structure or function in frontal, temporal and occipital regions (Feldmann et al, 2008; Gou et al, 2018; Mayberg et al, 1990; Nagy & Schrag, 2019), which corresponded with our findings and indicated serious brain damage in the S‐depression subtype. Additionally, enhanced functional connectivity in the cerebellum and thalamus was also observed in the S‐depression subtype.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the S‐motor subtype exhibited moderately disrupted local and global functions in the depression‐related pattern. Depression is a general neuropsychiatric symptom in PD (Nagy & Schrag, 2019). Although the S‐motor subtype was characterized by motor impairments, they might present with depression‐related symptoms, which was supported by the relatively higher depression‐related scores in the S‐motor subtype compared with normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety are common features of PD that are both responses to the illness and integral components of the disease process [3,11,[44][45][46]. It is difficult to extricate those components that reflect daily events, such as frustration with completing activities of daily living and the cycles of symptomatic drug effect and the approach of 'OFF' periods, and events that reflect the widespread pathology of PD altering those parts of the circuitry that control mood and psychological state in general [47].…”
Section: A Role For Adenosine a 2a Receptor Antagonists In The Treatmmentioning
confidence: 99%
“…Depression is a highly prevalent comorbidity of PD, with prevalence estimates ranging from 22% to 91% [2][3][4] and estimates of concomitant anti-parkinsonian and antidepressant use in older adults ranging from 25% to 58% of patients [5,6], with selective serotonin reuptake inhibitors emerging as the most frequently used antidepressant [5,6]. Moreover, depression is a key predictor of health-related quality of life, with increasing severity corresponding to decreased quality of life [7,8]. While depression principally impacts mental and emotional aspects of quality of life [9], it may also exacerbate motor symptoms [10] and alter patient self-perception of motor function [11].…”
Section: Introductionmentioning
confidence: 99%